Effects of trying to gain distance on golf driving technique - Buzza, S. J.; Irwin, G.; Bezodis, I. N.; Kerwin, D. G.; Kwon, Y. H. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Previous biomechanical research of the golf swing has shown segment separation of the shoulders and hips aids ball velocity. The purpose of the current study was to examine how the swing may differ when "trying" to gain extra distance in a game specific situation and whether an increase in launch velocity was achievable. A single subject design was employed with kinematic data (200 Hz) and ball characteristics collected using Trackman Pro launch monitor (ISG A/S, Denmark). Segment separation of the shoulder and hips (X-Factor and X-Factor stretch) and maximum endpoint velocity of the left hip, shoulder and elbow showed a significant difference between conditions, although mean launch velocity did not. This finding shows although the subject was able to produce greater endpoint velocity, performance improvement did not occur.